Negotiating Jewishness: Paul's ethnicity between continuity and discontinuity - Bühner, Ruben A. (Baylor University Press, 2025)
"Proposes a new model for understanding Paul's relationship with Judaism through the lens of rhetoric and the social construction of ethnic identity"-- Provided by publisher